ANALISIS KINERJA KEUANGAN KOPERASI CREDIT UNION HARAPAN KASIH KABUPATEN KUTAI BARAT - Titin Ruliana, Enus Sanusi, Elfreda Aplonia Lau (EKONOMIA, 2016)
The purpose of the research conducted to know how the credit union,s financial permance expectations of love. From the aspeck of liquidity, solvance and profitability according to the decision of the ministry of coorperative ans Smes RI 2004. Formula of is problem of do monetary performance at Credit Union Expectation Love seen from aspect of Likuiditas, Solvability and Rentability in the year 2012 and 2013 categorized by goodness pursuant to decision of kementrian of Co-Operation and of UKM RI 2004. Used by Theory base is monetary management which focus at monetary performance. Analyzer the used is likuiditas, rentability and solvability. Hypothesis research of monetary performance evaluated from aspect of Likuiditas, Solvability and Rentability of Credit Union Expectation Love in the year 2012 and 2013 categorized by goodness pursuant to decision of kementrian of Co-Operation and of UKM RI 2014. Result of research of year 2012 and 2013 designating that Likuiditas Solvability and Rentability of Credit Union Expectation Love year 2012 and 2013 categorized by goodness pursuant to decision of kementrian of and co-operation of UKM RI year 2004. Matter this means Credit Union Expectation Love can fulfill obligation short-range and also is long-range.Than result of research can be concluded that as a whole analysed ratios have yielded good ratio and have been categorized pursuant to decision of kementrian of and co-operation of UKM RI 2004. The finding support raised hypothesis, Monetary performance of Co-Operation Expectation Love evaluated from aspect of likuiditas, rentability and solvability in the year 2012 and 2013 in good value.